BURKHOLDERIA MALLEI ISOLATION FROM MILK OF A MARE AND EVIDENCE OF CONGENITAL TRANSMISSION OF GLANDERS IN EQUIDS: CASE REPORTS - NASSAR, A. F. C.; DEL FAVA, C.; TESSLER, D. K.; CASSIANO, L. L.; LEZIER, D. H.; GUNNEWIER, M. F. K.; MAGRINHO, F.; PITUCO, E. M.; CHIEBAO, D. P. (Ars Veterinaria, 2020)
This is the first report of Burkholderia mallei isolation in milk from a mare diagnosed with glanders and of transplacental transmission of the bacteria in a seropositive pregnant mare, both from São Paulo State, Brazil, 2016 and 2019. After necropsy, the horses were evaluated for macroscopic lesions, and organ samples were removed for histological, bacteriological, and molecular analysis. B.mallei was identified in milk samples by culture isolation and PCR, whereas in the fetus of the pregnant mare by PCR of the stomach fluid. These findings will contribute to the epidemiological knowledge of glanders life cycle in Brazil.